2021
DOI: 10.1128/spectrum.00823-21
|View full text |Cite
|
Sign up to set email alerts
|

Mr-AbaA Regulates Conidiation by Interacting with the Promoter Regions of Both Mr-veA and Mr-wetA in Metarhizium robertsii

Abstract: Metarhizium robertsii is an emerging model entomopathogenic fungus for developing biopesticides; therefore, a comprehensive understanding of its conidiation is very important for its application. In this study, we revealed that the transcription factor Mr-AbaA is involved in the control of aerial conidiation and blastospore separation in submerged culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Notably, in A. oligospora , loss of AoPEX1 and AoPEX6 leads to complete elimination of sporulation, differing from the marked reduction in conidiation caused by AaPEX6 mutation in A. alternata ( 30 ). The eliminated sporulation capacity correlated with transcriptional repression of several sporulation-related genes in the Δ Aopex1 and Δ Aopex6 mutants ( 31 ). In addition, the number of nuclei in each hyphal cell was markedly decreased in Δ Aopex1 and Δ Aopex6 mutants than that in the WT strain.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, in A. oligospora , loss of AoPEX1 and AoPEX6 leads to complete elimination of sporulation, differing from the marked reduction in conidiation caused by AaPEX6 mutation in A. alternata ( 30 ). The eliminated sporulation capacity correlated with transcriptional repression of several sporulation-related genes in the Δ Aopex1 and Δ Aopex6 mutants ( 31 ). In addition, the number of nuclei in each hyphal cell was markedly decreased in Δ Aopex1 and Δ Aopex6 mutants than that in the WT strain.…”
Section: Discussionmentioning
confidence: 99%
“…In Aspergillus conidia, Myb-like DNA-binding protein FlbD delivers signals to activate the conidiogenesis regulatory cascade BrlA-AbaA-WetA [ 32 ]. In Metarhizium robertsii , AbaA interacts with the promoter regions of VeA and WetA , contributing to the separation of blastospores in submerged culture [ 33 ]. Therefore, we tested the expression levels of the homologs of FlbD (KDB18803), BrlA (KDB11753), AbaA (KDB11305), and WetA (KDB15008) in U. virens at the initial stage of chlamydospore and conidia formation [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…Three transcription factors of this pathway, BrlA, AbaA, and WetA, coordinate conidiation-specific gene expression, and cause the marked increase in conidiation in Fusarium graminearum and Penicillium digitatum [ 36 , 37 ]. Mr-AbaA positively regulates conidiation by regulating the orthologous gene of velvet family Mr-veA in Metarhizium robertsii [ 33 ]. The VelB-VosA hetero-dimer plays a role of the negative feedback regulation of the brlA gene in the conidia [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Aspergillus, NsdD can negatively regulate expression of BrlA (Lee et al, 2016), and AbaA is a downstream of the regulatory gene BrlA (Adams et al, 1988). A recent study showed that AbaA can regulate VeA and WetA to participate in the conidiation of M. robertsii (Wu et al, 2021). Revealed in qPCR, Y1H and EMSA, MaNsdD enabled to directly regulate expression of AbaA.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that AbaA can regulate VeA and WetA to participate in the conidiation of M . robertsii (Wu et al ., 2021). Revealed in qPCR, Y1H and EMSA, MaNsdD enabled to directly regulate expression of AbaA .…”
Section: Discussionmentioning
confidence: 99%